LncRNAs Associated with Chemoradiotherapy Response and Prognosis in Locally Advanced Rectal Cancer - Zhang Y; Guan B; WU Y; Du F; Zhuang J; Yang Y; Guan G; Liu X (Dove Medical Press, 2021)
Yiyi Zhang,1,* Bingjie Guan,2,* Yong WU,1,* Fan Du,3,* Jinfu Zhuang,1 Yuanfeng Yang,1 Guoxian Guan,1 Xing Liu1 1Department of Colorectal Surgery, The First Affiliated Hospital of Fujian Medical University, Fuzhou, People's Republic of China; 2Department of Radiation Oncology, Fujian Medical University Union Hospital, Fuzhou, People's Republic of China; 3Department of Gastroenterology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 330006, People's Republic of China*These authors contributed equally to this workCorrespondence: Xing Liu; Guoxian GuanDepartment of Colorectal Surgery, The First Affiliated Hospital of Fujian Medical University, 20 Chazhong Road, Fuzhou City, 350001, Fujian, People's Republic of ChinaEmail fjmufylx@163.com; fjxhggx@163.comBackground: There are only limited studies on the long non-coding RNAs (lncRNAs) associated with neoadjuvant chemoradiotherapy (NCRT) response and prognosis of locally advanced rectal cancer (LARC) patients. This study identified lncRNAs associated with NCRT response and prognosis in CRC patients and explored their potential predictive mechanisms.Methods: The study subjected the LncRNA expression profiles from our previous gene chip data to LASSO and identified a four-lncRNA signature that predicted NCRT response and prognosis. A Cox regression model was subsequently performed to identify the prognostic risk factors. The function of LINC00909, the lncRNA with the most powerful predictive ability, was finally identified in vivo and in vitro using CRC cell lines.Results: A comparison of the relative lncRNA expression of NCRT-responsive and non-responsive patients revealed four hub lncRNAs: DBET, LINC00909, FLJ33534, and HSD52 with AUC = 0.68, 0.73, 0.73, and 0.70, respectively (all p < 0.05). COX regression analysis further demonstrated that DBET, LINC00909 and FLJ33534 were associated with the DFS in CRC patients. The expression of the four lncRNAs was also significant in LARC patients who had not undergone NCRT (all p < 0.05). A risk score model was subsequently constructed based on the results of the multivariate COX analysis and used to predict NCRT response and prognosis in the CRC and LARC patients. The expression and prognosis of DBET, LINC00909 and FLJ33534 in the CRC tissues were further validated in the R2 platform and Oncomine database. Notably, overexpression of the LINC00909 increased the cell line resistance to the 5-FU and radiotherapy in vivo and in vitro.Conclusion: DBET, LINC00909, and FLJ33534 are potential novel biomarkers for predicting NCRT response and prognosis in CRC patients. In particular, LINC00909 is an effective oncogene in CRC that could be used as a novel therapeutic target to enhance NCRT response.Keywords: rectal cancer, chemoradiotherapy, lncRNA, prognosis